AMELIORATIVE POTENTIAL OF ETHANOL LEAF EXTRACT OF ANNONA CHERIMOLA IN ALLOXAN-INDUCED DIABETIC RATS - Oniemola, Joan Mayowa; Ekeyi, Yusuf; Olorunnado, Gabriel Babatunde (FUDMA JOURNAL OF SCIENCES, 2023)
Diabetes mellitus (DM) is a chronic disease characterized by a relative or absolute lack of insulin secretion or insulin inaction. The study investigated the effect of Annona cherimola leaf extract on the liver and kidney function indices of alloxan-induced diabetic rats. A total of twenty (20) albino rats of both sexes weighing about 100g to 200g were used for the study, while eighteen (18) mice were used for the acute toxicity study. The animals were randomly divided into five (5) groups of four (4) rats each; Group 1 was not induced nor treated (normal control), group 2 was induced but not treated (untreated control), group 3 was induced and treated with 100 mg/kg b.w. of metformin (standard control), and groups 4 and 5 were induced and treated with 100 and 200 mg/kg b.w. of the extract respectively. The induction of diabetes was achieved by intraperitoneal injection of alloxan monohydrate (150 mg/kg b.w.). The oral administration (treatment) was done once per day using gavages for fifteen (15) days, and the blood glucose level was checked every three (3) days. The result indicated the extract possessed significant (p < 0.05) antidiabetic effect on groups 4 and 5 compared to the untreated group. A significant (p < 0.05) increase in serum total cholesterol (TC) and triglyceride (TAG) was also observed in groups 4 and 5 compared to the untreated group. In conclusion, this research showed that the ethanol leaf extract of Annona cherimolapossess a potent ameliorative effect in alloxan-induced diabetic rats.